Ele é agressivo, mas é meu marido: reincidência de violência física conjugal contra a mulher na cidade de Vitória-ES (2004 2010) - Silva, Renata Alves da (2018)
This dissertation aims to characterize the practice of recidivism of conjugal physical violence against women in their theoretical-conceptual perspectives, their representations in the construction of socioeconomic and cultural values that stereotype for women a certain social role. Recidivism refers to repeated actions. It is, therefore, a phenomenon of reiteration of physical violence against women and gender, observed within the framework of the conjugal relationship, sometimes naturalized, from the symbolic value that constitute the defined patterns within the scope of male domination. In this perspective, the feminist movement appears in this work as an expression of the struggle for equality and equality of rights, elucidating the recurrence of violence suffered by women in marital relations. For this purpose, a survey was carried out on the case reports recorded at the Specialized Vicariate for Women in Vitória - ES (DEAM / Vitória) from the case study method, between 2004 and 2010. The theoretical categories that guided this research are based on Pierre Bourdieu's propositions on the symbol and its meanings, as well as on the considerations made by Heleieth Iara Bongiovani Saffioti and Joan Wallach Scott when discussing the concept of gender. The results show that the social values constituted from the patriarchal system are perceived through male domination, the construction of the socioeconomic and cultural values that generate for the woman the submission, favoring violent relations. Thus, the home is no longer the safest place for women, since the recurrence of violence is linked to the domestic space and the conjugal relationship. Therefore, it is expected that this dissertation contributes as a source of evidence of marital physical recidivism to which women are exposed and that it collaborates with alterations in the socioeconomic and cultural representations that foment the permanence of the violence against the naturalized woman in the conjugal relations.